Advanced Composites Inspired by Biological Structures and Functions in Nature: Architecture Design, Strengthening Mechanisms, and Mechanical‐Functional Responses - Hanqing Dai; Wenqing Dai; Zhe Hu; Wanlu Zhang; Guoqi Zhang; Ruiqian Guo (Advanced Science)
Abstract The natural design and coupling of biological structures are the root of realizing the high strength, toughness, and unique functional properties of biomaterials. Advanced architecture design is applied to many materials, including metal materials, inorganic nonmetallic materials, polymer materials, and so on. To improve the performance of advanced materials, the designed architecture can be enhanced by bionics of biological structure, optimization of structural parameters, and coupling of multiple types of structures. Herein, the progress of structural materials is reviewed, the strengthening mechanisms of different types of structures are highlighted, and the impact of architecture design on the performance of advanced materials is discussed. Architecture design can improve the properties of materials at the micro level, such as mechanical, electrical, and thermal conductivity. The synergistic effect of structure makes traditional materials move toward advanced functional materials, thus enriching the macroproperties of materials. Finally, the challenges and opportunities of structural innovation of advanced materials in improving material properties are discussed.